Study of Technoeconomic Synthetic Bone Ash Production - Abdul Rachman; Kristanto Wahyudi (Jurnal Keramik dan Gelas Indonesia, 2017)
Balai Besar Keramik has succeeded in producing synthetic bone ash from natural limestone and phosphoric acid. Characteristic of synthetic bone ash has a purity of  ≥  98%, white degree (brightness 90.59 and whiteness 89,42), ratio of Ca / P 1,64. Synthetic Bone ash is not inferior to bone ash from bovine bone combustion so it can be used as an alternative raw material for bone china ceramic body. The technoeconomic studies have been analyzed with assumption for the production capacity of 30 tons per month of synthetic bone ash, 5 years investment age will require initial investment cost of Rp. 3,667,083,700, - and total production cost per year is Rp. 4.059.279.000, -. With the selling price of synthetic bone ash products Rp.16.000, - / kg, will get the value of NPV in the 5th year of Rp. 557.517.242,27, -, IRR of 18.36%,  BCR of 1,135, BEP units: 982,774 kg, BEP sales: Rp. 15,724,389,020, - and Payback Period is 3.08 years. The results indicate that bone ash production is feasible according to financial criteria.